2019
DOI: 10.1186/s40360-019-0299-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of albendazole tablets legally circulating in the pharmaceutical market of Addis Ababa, Ethiopia: physicochemical evaluation

Abstract: Background Parasitic diseases are the main challenge of livestock production in the world. They are mainly controlled by the use of anthelmintic drugs. To be effective, the drugs should contain the appropriate amount of active pharmaceutical ingredient (API) and have the required physical characteristics. In this study, qualitative and quantitative assessments were performed to evaluate the quality of different brands of albendazole tablets legally circulating in pharmaceutical markets of Addis Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 17 publications
6
26
0
Order By: Relevance
“…In this study, 22.2% of the brands or 23.1% of batches didn't have leaflets or package inserts. The absence of leaflet was also reported by Seifu et al (2019) for albendazole in the same study area. This may lead to the inappropriate use of the drugs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this study, 22.2% of the brands or 23.1% of batches didn't have leaflets or package inserts. The absence of leaflet was also reported by Seifu et al (2019) for albendazole in the same study area. This may lead to the inappropriate use of the drugs.…”
Section: Discussionsupporting
confidence: 80%
“…Hence, periodic assessment of drugs circulating in the market will make the quality control process complete and help to design systems or strategies to control the circulation of substandard drugs. The authors of this article conducted a quality test on albendazole, a quite commonly used drug to treat helminthic parasites, and found that 3 of the 10 batches contained a lower amount of albendazole per tablet than expected (Seifu et al, 2019). This finding initiates us to test the quality of other drugs like oxytetracycline which is quite commonly sold and used drug for the treatment of widespread infectious diseases in animals (Tufa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“… 18 Seifu et al found that all batches of albendazole circulating in the market in Addis Ababa did not fulfill either physical or chemical quality standards. 19 These findings revealed that the Ethiopian health system could be endangered with poor quality medicines. Hence, there is the need for continuous assessment of the pharmaceutical quality of essential drugs circulating in the market to ensure the quality of these medicines.…”
Section: Introductionmentioning
confidence: 99%
“…The severe consequences for end customers as patients in taking counterfeit products are an additional societal burden. The process activities labelled CO, are those supply chain processes which, from the insight of the case study supported by Seifu et al (2019) and Suleman et al (2014), are possible gateways for counterfeited products into the legitimate chain. The tracing (Tr) and inventory management (IM) categories both affect efficiency.…”
Section: Results Data Analysis and Discussionmentioning
confidence: 99%